Selective Optimization of Pranlukast to Farnesoid X Receptor Modulators. (20th November 2018) - Schierle, Simone; Schmidt, Jurema; Kaiser, Astrid; Merk, Daniel
Abstract: Selective optimization of side activities (SOSA) offers an alternative entry to early drug discovery and may provide rapid access to bioactive new chemical entities with desirable properties. SOSA aims to reverse a drug's side activities through structural modification and to design out the drug's original main action. We identified a moderate side activity for the cysteinyl leukotriene receptor 1 (CysLT1 R) antagonist pranlukast on the farnesoid X receptor (FXR). Systematic structural modification of the drug allowed remarkable optimization of its partial FXR agonism to sub‐nanonmolar potency. The resulting FXR modulators lack any activity on CysLT1 R and are characterized by high selectivity, high metabolic stability, and low toxicity. With their favorable in vitro profile, these SOSA‐derived FXR modulators constitute a new FXR ligand chemotype that appears suitable for further preclinical evaluation. Abstract : Side dish becomes main course : We identified a moderate side activity for the cysteinyl leukotriene receptor 1 (CysLT1 R) antagonist pranlukast at the farnesoid X receptor (FXR). It is a weak FXR agonist, yet was optimized to highly selective FXR modulatory potency by systematic structural modification according to the selective optimization of side activities (SOSA) strategy.